2008
DOI: 10.1111/j.1745-7262.2008.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile function after urethral reconstruction

Abstract: Advances in urogenital plastic surgical tissue transfer techniques have enabled urethral reconstruction surgery to become the new gold-standard for treatment of refractory urethral stricture disease. Questions remain, however, regarding the long-term implications on sexual function after major genital reconstructive surgery. In this article, we review the pathologic features of urethral stricture disease and urologic trauma that may affect erectile function (EF) and assess the impact of various specific contem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…It is this parameter that governs which reconstructive procedure should be selected. Carlton et al [7] found that men undergoing repair of longer strictures report erectile dysfunction more often. In our study, when different stricture lengths were compared, patients with 16 cm of strictured urethra had comparatively lower sexual desire (mean SD score of 5.78).…”
Section: Discussionmentioning
confidence: 99%
“…It is this parameter that governs which reconstructive procedure should be selected. Carlton et al [7] found that men undergoing repair of longer strictures report erectile dysfunction more often. In our study, when different stricture lengths were compared, patients with 16 cm of strictured urethra had comparatively lower sexual desire (mean SD score of 5.78).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of urethral stricture is always a great challenge for urologists, although a paradigm shift in managing this disease has occurred within the past decades. In addition to attaining meaningful improvement in voiding efficiency and alleviating symptoms, satisfaction with remaining erectile function after surgery is also an important criterion of ideal postoperative outcome for urethroplasty .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering is one of the exciting areas in biotechnology. It combines the principles and methods of the life sciences with those of engineering to elucidate fundamental understanding of structure-function relationships of normal and diseased tissue to facilitate the development of materials and methods to repair damaged diseased tissue and create entire tissue replacement [1][2][3]. In our previous study, foreskin epidermal cells successfully replaced urethral epithelium cells in urethra reconstruction [4].…”
Section: Introductionmentioning
confidence: 99%